1971
DOI: 10.1139/e71-137
|View full text |Cite
|
Sign up to set email alerts
|

Fission Track Ages of some Indian Muscovites

Abstract: Seven samples of muscovite from three main mica-producing regions of India, i.e. Rajasthan, Bihar, and Andhra Pradesh, have been dated by the fission track technique. The geological annealing of fossil radiation damage has been assessed by comparative study of induced and fossil track lengths. The uranium concentration has been measured in tight cleavages so as to avoid errors due to contamination. The measured ages give an indication of the main orogenic metamorphic cycles in the respective regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1974
1974
1979
1979

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…It is known that the fission track ages of biotite and other minerals may be discordant with the real age of the mineral determined by the K-Ar or Rb-Sr methods (MEIER, 1966;WAGNER, 1973;WELIN et al, 1972;OSBORNE, 1947;LAKATOS and MILLER, 1973;BIGAZziet al, 1971;MILLER and JAGER, 1968;MILLER, 1968;GUPTA et al, 1971). For instance, younger fis sion track ages are caused by thermal annealing of fission tracks (HAACK and POTTS, 1972) in accordance with eq.…”
Section: Ormentioning
confidence: 97%
See 1 more Smart Citation
“…It is known that the fission track ages of biotite and other minerals may be discordant with the real age of the mineral determined by the K-Ar or Rb-Sr methods (MEIER, 1966;WAGNER, 1973;WELIN et al, 1972;OSBORNE, 1947;LAKATOS and MILLER, 1973;BIGAZziet al, 1971;MILLER and JAGER, 1968;MILLER, 1968;GUPTA et al, 1971). For instance, younger fis sion track ages are caused by thermal annealing of fission tracks (HAACK and POTTS, 1972) in accordance with eq.…”
Section: Ormentioning
confidence: 97%
“…Moreover, in such mica large cleavage layers which are characterized by an uniform uranium distribution (GUPTA et al, 1971) and, as a consequence, which are not disturbed by halos may be eventually suitable for dating. 2.…”
Section: Ormentioning
confidence: 99%
“…The literature presents divergent views about the annealing correction in muscovite. Mehta and Rama,' Mehta and Nagpaul' and Gupta et al 3 concluded from their studies o f fission track ages of muscovite samples collected from all three mica fields of India, that in most cases, correction is not needed. A calibration curve drawn by Mehta and Rama' for muscovite indicates that up to 40% of track shrinkage n o density reduction is observable.…”
Section: Introductionmentioning
confidence: 99%